Effect of Natural Zeolite on Performance of Sulfoaluminate Cement-based Planting Cementitious Material - 李来波 宫晨琛 WANG Shoude LU Lingchao CHENG Xin (Journal of Wuhan University of Technology. Materials science edition, 2017)
This paper aimed to improve the water-retention performance and basic physical properties of sulfoaluminate cement（SAC）-based planting cementitious material. The effect of natural zeolite on the performance of SAC-based planting material was investigated. The water-retention performance, porosity, compressive strength, and alkalinity had been tested and TG-DSC analysis had been adopted in this paper. Experimental results showed that zeolite was effective to improve the water-retention capacity and 10%, 20% and 30% natural zeolite increased the pore volume of the hardened pastes by 10.6%, 26.0%, and 38.6%, especially pore size below 0.1 μm was increased by 9.7%, 26.2% and 17.5%. And 10% zeolite was beneficial to the compressive strengths of cementitious material and 1, 3, and 28 d compressive strength reached up to 35.9, 55.0, 80.3 MPa. Furthermore zeolite decreased the alkalinity of pore fluid of hardened cementitious material, while the addition of zeolite reached up to 30%, the alkalinity of pore fluid of hardened cementitious material decreased by 8.9%. Therefore zeolite was suitable for improving the performance of SAC-based planting cementitious material.